Dampak Corporate Social Responsibility pada Kinerja Keuangan yang Dimoderasi Ukuran Perusahaan (Studi Empiris Pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia Tahun (2021) - Verliani Dasmaran; Fauziah Fika (Jurnal Akuntansi, 2022)
This study aims to obtain empirical evidence regarding the Effect of Corporate Social Responsibility on Financial Performance with Company Size as a Moderating Variable listed on the Indonesia Stock Exchange in 2021. The population in this study are LQ45 companies listed on the Indonesia Stock Exchange. The number of research samples is 45 companies. The data analysis technique used is saturated sampling technique, with regression, correlation and determination tests. The results of the study prove that Corporate Social Responsibility has a positive effect on Financial Performance, this is because the complete disclosure of Corporate Social Responsibility activities can convince investors or stakeholders in carrying out their responsibilities. While company size can moderate the effect of Corporate Social Responsibility on Financial Performance, this proves company size can increase the trust of external parties in carrying out corporate responsibility Keywords: corporate social responsibility. company size, financial performance